The COVID-19 pandemic impact on the Portuguese Physical Education classes - Pedro Cabral Mendes; Miguel Fachada; Ricardo Melo; Francisco Campos; Paulo Nobre; Aristides M. Machado-Rodrigues (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The restrictions “imposed” to avoid the spread of Covid-19 disease have strongly conditioned the school life of millions of children and youth. However, little is known about the impact of the pandemic on PE classes in Portugal. The purpose of the present study is to describe the perception of secondary and high school students about the impact of the pandemic on PE classes, after the first wave of the COVID-19 outbreak. The sample comprised 1419 students aged from 12 to 16 years from the Portuguese Midlands (53% females, mean age 14,4 years-old); participants responded in person to an anonymous and self-report questionnaire. The results revealed that restrictive measures imposed on PE classes at the end of 2020 had a strong influence on selection of PE curricular contents. Physical condition of students has assumed a major role in PE enrolment. It should be also highlighted that participants revealed the school as a safe space to avoid the risks of SARS-CoV2 contagion. The surveyed students expressed greater satisfaction with the face-to-face than virtual PE classes. It should be noted that the pandemic context did not change the appreciation attributed to this subject by students.